Empathy-Based Learning Model to Enhance Social-Emotional Development in Early Childhood - Syaiful Amri; Putra, Bramana Nanditya; Dwi Noviana Komsi (Journal of Childhood Development, 2025)
This study aims to analyze the influence of empathy-based learning models on the social and emotional development of early childhood in Lubuk Linggau City. The background to this research stems from the fact that many early childhood education institutions still focus on academic skills, resulting in underdevelopment of social and emotional aspects. This is despite the fact that the ages of 4–6 are considered the golden age. Age is a period when empathy, emotional regulation, and social interaction skills experience rapid development and are greatly influenced by the quality of the learning environment. This study used a quantitative approach. The research sample consisted of children aged 5–6 years and teachers from several early childhood education institutions in Lubuk Linggau City selected through purposive sampling. The research instruments were validated questionnaires and observation sheets, while data analysis was conducted using paired t-tests and simple regression. The results showed a significant increase in children's social-emotional abilities after participating in an empathy-based learning model. The average score increased from 62.14 (moderate category) to 81.72 (good category), with a t-value of 9.87 and a significance level of 0.000 (p < 0.05). Improvements occurred in all social-emotional indicators, namely empathy (32%), prosocial behavior (31%), positive social interaction (29%), emotional regulation (28%), and the ability to cooperate (25%). These findings confirm that the empathy-based learning model is effective in improving the social-emotional competence of early childhood. This study recommends that PAUD institutions integrate empathy-oriented learning strategies more systematically to strengthen social-emotional skills as the foundation of child development.